What are the determinants of underpricing in Initial Public Offerings? Evidence from Indonesia - Heriyanto Heriyanto; Ming Chen; Erni Lyani (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to investigate the impact of different variables, including firm size, underwriter reputation, firm age (representing asymmetric information), board ownership, institutional ownership (representing ownership structure), industry sector (financial or non-financial), and ownership status (state-owned or non-state-owned enterprises) on the initial return, which serves as a measure of underpricing level.Method — We focus on companies that underwent initial public offerings (IPOs) between 2010 and 2019. For our study, we selected a sample of 261 firms using the purposive sampling technique. To analyze the data, we employed a multiple linear regression model and utilized SPSS as a testing tool.Result — Based on our research findings, we have identified that firm size, underwriter reputation, and institutional ownership significantly affect the level of underpricing. However, we found no evidence to suggest that factors such as company age, board ownership, industry sector, or ownership status have any impact on the underpricing level. Our results support the notion that asymmetric information plays a crucial role in explaining the observed underpricing phenomenon in IPOs, while industry type and ownership structure do not contribute to its explanation.Contribution — This study makes a valuable contribution to the existing research on IPO underpricing in Indonesia. It stands out by employing a comparatively long research period and incorporating not only variables that address asymmetric information but also variables pertaining to governance mechanisms, specifically board ownership and institutional ownership.